Effectiveness of Lecture with Demonstration Method on Maternal Knowledge about Growth and Development of Toddlers - Zubaeda; Suryanti Tukiman; Nilan (Viva Medika, 2024)
Growth and development are indicators of life achieved by humans from conception to adulthood (Faizah, 2020). An important period in a child's growth and development is the toddler stage, as this phase forms the foundation that will influence and determine the child's future development (Ayunita, 2017). At the Kairatu Barat Community Health Center, there is a Posyandu (Integrated Service Post) called Diaspora. A survey revealed that health promotion staff there always use the lecture method, which makes mothers of toddlers feel bored and inattentive to the counseling. This study aims to determine the effect of counseling using lecture and demonstration methods on mothers' knowledge about the growth and development of toddlers aged 3-5 years. This quasi-experimental study used a "two group pretest-posttest" research design. The population comprised 26 mothers with toddlers aged 3-5 years, all of whom were used as the research sample. Data was collected using a questionnaire to measure knowledge levels. Analysis using the Wilcoxon test showed that counseling using lecture (p=0.010) and demonstration (p=0.001) methods influenced the increase in mothers' knowledge. Meanwhile, the Mann-Whitney test showed that the demonstration method was more effective in increasing mothers' knowledge about the growth and development of toddlers aged 3-5 years (p=0.000).